Harmony in the Workplace: Decoding the Psychology of Effective Human Resource Management - Risman Nugraha (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This article delves into the intricacies of the relationship between psychology and human resource management (HRM) in the context of the modern workplace. With a focus on fostering harmony in the workplace, the article explores ways to understand and manage employees' psychological aspects to enhance performance and satisfaction within the organization. Through a thorough examination of psychological theories and HRM principles, this article explores how a profound understanding of individual psychological needs can shape inclusive and sustainable HRM policies. Thus, the article not only discusses theories but also offers practical insights to assist organizations in achieving an optimal balance between psychology and HRM